ECOLOGICAL CHARACTERISTICS OF POME PONDS WITH REFERENCE TO STUDY SOME OF THEIR INVERTEBRATE SPECIES IN PENINSULAR MALAYSIA - A. B. Hassen-Aboushiba; R. Ramli; M. Sofian-Azirun (Journal of Animal and Plant Sciences, 2013)
Food is major factor for the survival of avian species and play significant role in their distribution and habitat selection. The food resources of POME ponds were examined using scoop net (a metal container) and avian species were determined direct visual observation from January to June, 2010. A total of 119126 invertebrate individuals of twelve species were recorded from POME pond number one and three. However, no individual was sampled from pond number two and four. Mosquito Larvae – Aedes sp. (40.71%) was the most abundant invertebrate species and Water Scavenger Beetles – Hydrophilus sp. (2.52%) was the rarest one. The relative abundance of aquatic invertebrate was significantly different in pond number one (i.e. F11, 60 = 37.86, P < 0.05) and three (i.e. F11, 60 = 34.23, P < 0.05). For POME pond number one, the higher species diversity, i.e. Shannon’s (N1 = 2.21), and species evenness, i.e. Pielou’s J (E = 0.89) was determined in June and species richness, i.e. Margalef’s (R1 = 1.73) in May. In contrast, the lowest species diversity i.e. Shannon’s N1 = 0.66, species richness, i.e. Margalef’s (R1 = 0.35), and species evenness, i.e. Pielou’s J (E = 0.47) was recorded in January. Similarly, for POME pond number three, the highest invertebrate species diversity i.e. Shannon’s (N1 = 2.17) and evenness i.e. Pielou’s J (E = 0.87) was recorded in June and the lowest invertebrate species diversity (N1 = 0.59) and evenness (E = 0.42) was recorded in January. Likewise, the highest species richness such as Margalef’s (R1 = 1.19) was recorded in March and the lowest (R1 = 0.34) in January. In addition, direct observation detected twenty one waterbird species that frequently utilized POME ponds for foraging and loafing purpose. The results of this study highlighted that POME ponds are highly productive and attractive habitats for diverse avian species particularly waterbirds due to occurrence of different invertebrate species.
Keywords: Invertebrates; POME; Scoop net; Diversity; Aves; Island